Genome-wide analysis of the ERF Family in Stephania japonica provides insights into the regulatory role in Cepharanthine biosynthesis - Yang, Hanting; Liu, Baimei; Ding, Haiyan; Liu, Zhaoyu; Li, Xiaodong; He, Tianxing; Wu, Ya; Zhang, Yuxuan; Wang, Can; Leng, Liang; Chen, Shilin; Song, Chi (Frontiers in Plant Science, 2024)
Cepharanthine (CEP), a bisbenzylisoquinoline alkaloid (bisBIA) extracted from Stephania japonica, has received significant attention for its anti-coronavirus properties. While ethylene response factors (ERFs) have been reported to regulate the biosynthesis of various alkaloids, their role in regulating CEP biosynthesis remains unexplored. In this work, 59 SjERF genes were identified in the S. japonica genome and further categorized into ten subfamilies. Notably, a SjERF gene cluster containing three SjERF genes was found on chromosome 2. Yeast one-hybrid assays confirmed that the SjERF gene cluster can directly bind to the promoters of several CEP-associated genes, suggesting their crucial role in CEP metabolism. The SjERFs cluster-YFP fusion proteins were observed exclusively in the nuclei of Nicotiana benthamiana leaves. Tissue expression profiling revealed that 13 SjERFs exhibit high expression levels in the root, and the qRT-PCR results of six SjERFs were consistent with the RNA-Seq data. Furthermore, a co-expression network analysis demonstrated that 24 SjERFs were highly positively correlated with the contents of various alkaloids and expression levels of CEP biosynthetic genes. This study provides the first systematic identification and analysis of ERF transcription factors in the S. japonica genome, laying the foundation for the future functional research of SjERFs transcription factors.